مستوى التنظيم الانفعالي لدى عينة من طالبات المرحلة الثانوية بمدينة جدة وعلاقته بالرضا عن الحياة - السلمي، صفية محمد; أكرم، هديل بنت عبدالله (المركز القومي للبحوث غزة, 2020)
هدفت هذه الدراسة إلى الكشف عن مستوى كل من التنظيم الانفعالي، والرضا عن الحياة، والتعرف على طبيعة العلاقة الارتباطية بينهما كمتغيرين أساسين، بالإضافة إلى معرفة الفروق بينهما، وفقا لمتغيري (الصف، والتخصص)، وقد تم التأكد الخصائص السيكومترية لأدوات الدراسة ومدى ملاءمتها للعينة، وكما تكونت عينة الدراسة الأساسية من (231) طالبة؛ وقد خرجت الدراسة بالعديد من النتائج كان من أهمها امتلاك عينة الدراسة مستوى متوسطا من التنظيم الانفعالي؛ ومستوى مرتفعا من الرضا عن الحياة، كما أظهرت النتائج وجود علاقة إيجابية ذات دلالة إحصائية بين التنظيم الانفعالي والرضا عن الحياة، وكذا وجود فروق ذات دلالة إحصائية في الدرجة الكلية للرضا عن الحياة تعزى لأثر متغير التخصص؛ لصالح التخصص الأدبي، وقد تم بناء على نتائج الدراسة، تقديم عدد من التوصيات، وكذا عدد من المقترحات موجهة إلى المؤسسات التعليمية، والقائمين على العملية الإرشادية بمدارس التعليم؛ أملا في أن تسهم في تطوير الخدمات الإرشادية المقدمة لطالبات المرحلة الثانوية.
This study aims to explore the level of both the emotional regulation, the life satisfaction, and the correlation relationship between them as a main variables in addition to identify the variance between them according to the two variables (class and the specialization), The psychometric features and the appropriateness of the study tools were insured. The main sample of the study consisted of (231) female student. The study found out that the study sample has an average level of the emotional regulation, and a high level of life satisfaction. In addition, it showed a positive relationship with statistically significant between the emotional regulation and the life satisfaction, it also showed a statistically significant difference in the total degree of the life satisfaction which refers to the impact of specialization variable in favor of the literacy specialization. Based on these findings, the study presented some of the recommendations to the educational institutions and to the responsible of the counseling process in the education schools, hoping to contribute in the development of the presented counseling services to the students of the secondary stage.
Keywords: علم النفس الاجتماعي -- جودة الحياة -- طلبة المرحلة الثانوية -- السعودية